2019
DOI: 10.1002/cne.24813
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of striatal phenotypes in heterozygous Disc1 mutant mice, a model of haploinsufficiency

Abstract: Disrupted‐in‐Schizophrenia 1 (DISC1) is a susceptibility gene for several psychiatric illnesses. To study the pathogenesis of these disorders, we generated Disc1 mutant mice by introducing the 129S6/SvEv 25‐bp deletion Disc1 variants into the C57BL/6J strain. In this study, we used heterozygous Disc1 mutant (Het) mice to evaluate the DISC1 haploinsufficiency model of schizophrenia. No changes in locomotor behaviors were observed in Het mice; however, after amphetamine injection, greater locomotor activity was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(20 citation statements)
references
References 86 publications
1
19
0
Order By: Relevance
“…In the present study, we showed an increased density of NeuN-positive neurons in the white matter of Disc1 Het mice, a haploinsufficiency model of schizophrenia (Juan et al, 2014;Baskaran et al, 2020). This finding was in line FIGURE 6 | Morphometric analysis of Type II layer VIb neurons.…”
Section: Increased White Matter Neurons In Disc1 Het Micesupporting
confidence: 88%
See 1 more Smart Citation
“…In the present study, we showed an increased density of NeuN-positive neurons in the white matter of Disc1 Het mice, a haploinsufficiency model of schizophrenia (Juan et al, 2014;Baskaran et al, 2020). This finding was in line FIGURE 6 | Morphometric analysis of Type II layer VIb neurons.…”
Section: Increased White Matter Neurons In Disc1 Het Micesupporting
confidence: 88%
“…We had established a Disc1 mutant mouse model, in which a 25-bp deletion variant of 129S6/SvEv Disc1 gene was brought to the C57BL/6J background by generations of backcrossing (Juan et al, 2014). Compared with other Disc1 mutant mice, our model exhibits relatively moderate abnormalities, suggesting that these mice are in a prodromal status (Juan et al, 2014;Baskaran et al, 2020). This model is therefore suitable for studies concerning the impact of environmental risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…We therefore suggest that our model might represent subjects in the prodromal states of SZ, in which predominant symptoms are not yet manifested [ 29 ]. In the following study, we further characterized the striatal phenotypes in Het Disc1 mice, an SZ model of haploinsufficiency [ 30 ]. We found biochemical and morphological changes in the striatum of Het Disc1 mice including the levels of dopamine (DA) receptors, GSK3, and PSD95 as well as the dendrites and spines of medium spiny neurons (MSNs) and density of parvalbumin (PV) neurons [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the following study, we further characterized the striatal phenotypes in Het Disc1 mice, an SZ model of haploinsufficiency [ 30 ]. We found biochemical and morphological changes in the striatum of Het Disc1 mice including the levels of dopamine (DA) receptors, GSK3, and PSD95 as well as the dendrites and spines of medium spiny neurons (MSNs) and density of parvalbumin (PV) neurons [ 30 ]. Notably, the effects of these changes are somewhat counterbalanced, resulting in normal locomotor activity in Het Disc1 mice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation